(untitled) (Research, Society and Development, 2020)
Objective: to understand the experience and daily life of women-mothers and caregivers of children with special health needs and the implications for their health. Methodology: qualitative research carried out with ten mothers of children with special health needs, through semi-structured interviews. Data processing took place with the aid of the IRAMUTEQ software. The data were organized into thematic categories with subsequent content analysis. Results: a textual corpus composed of 10 Initial Context Units or interviews was analyzed, in which 451 text segments or Elementary Context Unit and 345 analyzed segments were obtained, that is, 76.5% of the analyzed corpus. Mothers experience social isolation, overload of activities and physical exhaustion, resulting in the need for therapies and care to ensure their physical, psychosocial and emotional health. Final considerations: it became evident that being the mother of a child with special health needs represents a singularity with the object of care of this mother woman, also demonstrating a strong neglect in the health care of women-mothers in favor of their children.